THE IMPORTANCE OF ISLAMIC RELIGIOUS EDUCATION AND MORAL EDUCATION IN SHAPING THE CHARACTER OF ELEMENTARY SCHOOL STUDENTS - Retno Purwaningsih; Muhamad Slamet Yahya (LP2M IAI Al-Khairat Pamekasan, 2026)
This study examines the importance of Islamic Religious Education (PAI) and moral education in shaping the character of elementary school students in the modern era. Character is a fundamental foundation for children’s personality development that will determine their future. The research problem focuses on how PAI and moral education can play an optimal role in character formation among elementary school students, considering that the age period of 6–12 years is a critical stage for character development. The objective of this study is to analyze the role of PAI and moral education, identify effective implementation strategies, and provide development recommendations. The research method employs a qualitative approach through literature review and comparative analysis of various related studies. The findings indicate that PAI and moral education play a strategic role in shaping religious character, noble morals, and balanced personalities. Comparisons with previous studies show consistent findings regarding the importance of integrating religious and moral values in children’s education. The study concludes that synergy between PAI and moral education, supported by collaboration among all educational stakeholders, can optimize character development in elementary school students to face contemporary challenges